Effect of Proprioceptive Neuromuscular Facilitation on efficacy and pain relief for symptomatic shoulder conditions: A meta-analysis - Edmund Jia Xi Zhang; Yun Xiu Lam; Winston Shang Rong Lim; Denny Tjiauw Tjoen Lie (Journal of Orthopaedic Reports)
Objectives: Proprioceptive Neuromuscular Facilitation (PNF) is a rehabilitative technique widely used to enhance motor function and coordination in patients with neurological and orthopaedic conditions. This meta-analysis aims to review the existing literature to evaluate the effectiveness of PNF in managing symptomatic shoulder conditions. Design: A systematic search of the literature was performed in April 2024. Articles involving the use of PNF in the treatment of PT were included. Comparative meta-analysis was performed on articles reporting visual analogue scale (VAS) scores, range of motion (ROM), and Shoulder Pain and Disability Index (SPADI). Result: Nine studies consisting of 158 patients were identified. Mean follow-duration was 3.25 ± 1.20 weeks. VAS score improvement was −3.26 (CI: −4.33 to −2.20; P < 0.01). SPADI scores improved by −20.57 (CI: −47.92 to 6.78; P = 0.14). Abduction, external rotation, internal rotation and flexion all had significant improvement. Conclusions: PNF appears to be an effective intervention for improving pain and functional mobility in patients with various shoulder conditions. However, the clinical heterogeneity and variable methodology across studies highlight the need for standardized protocols and long-term effectiveness studies. Further research is required to refine PNF applications and evaluate its potential in post-operative rehabilitation.